FORMATION OF PHOTOSYNTHETIC PARAMETERS OF PLANTING AND BIOLOGICAL YIELD OF MILLET VARIETIES DEPENDING ON METHODS OF SOWING AND INTERCROPPING - Kostenko, M. (Scientific Progress & Innovations, 2022)
During the experiment, the influence of predecessors, sowing methods, and sowing rates on the productivity of millet was studied. The study aimed to estimate the impact of varieties, sowing methods, and precursors on the formation of photosynthetic indicators and the biological yield of millet. The leaf surface area was calculated by the method of cutouts. The accumulation of organic matter in plants was calculated by the weight method after drying the cuttings in a thermostat. After obtaining the relevant data, the photosynthetic potential and net photosynthetic productivity were calculated using formulas. The best results were observed in plants sown in a row method in soil free from crops. The Bila Altanka variety, sown in a row method in soil free from crops, had the best results in almost all indicators: leaf area – 57.4 m2/ha in the tuber phase and 58.3 m2/ha in the panicle ejection phase; photosynthetic potential – 579.07 thousand m2/ha; net productivity of photosynthesis – 8.8 g per day/m2; dry mass gain – 36.92 g per day/m2; plant weight – 723 g/m2; biological yield – 2.3 t/ha of grain and 4.8 t/ha of straw. The maximum foliage was also in the Bila Altanka variety, sown in a row method, but the predecessor was winter wheat. Foliage in this version was 47 %. The dependence between photosynthetic indicators and yield is observed. The greater the leaf area, the photosynthetic potential of the crop, net photosynthetic productivity, and dry weight gain, the better the yield. The Zolushka variety, sown in a row after predecessors such as peas and winter wheat, showed a high result compared to other options. Thus, the biological yield of Zolushka, sown by the row method after peas, was 1.6 t/ha of grain and 2.2 t/ha of straw, and after winter wheat – 1.3 t/ha of grain and 2.2 t/ha of straw. Most of the other indicators in these options are high. The worst results were in varieties sown after perennial grasses. Moreover, it was the Zolushka variety that showed the lowest results, even though they were high after other predecessors. Thus, the Zolushka variety, sown after perennial grasses in a row method had a yield of 0.4 t/ha of grain and 0.5 t/ha of straw, and in a wide-row method – 0.3 t/ha of grain and 0.4 t/ha of straw. We recommend the Zolushka variety for cultivation, sown in rows after peas.